2016
DOI: 10.1002/ecy.1496
|View full text |Cite
|
Sign up to set email alerts
|

Food web structure shaped by habitat size and climate across a latitudinal gradient

Abstract: Habitat size and climate are known to affect the trophic structure and dynamics of communities, but their interactive effects are poorly understood. Organisms from different trophic levels vary in terms of metabolic requirements and heat dissipation. Indeed, larger species such as keystone predators require more stable climatic conditions than their prey. Likewise, habitat size disproportionally affects large-sized predators, which require larger home ranges and are thus restricted to larger habitats. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 33 publications
1
60
1
1
Order By: Relevance
“…Diptera larvae are very abundant in bromeliads (Araújo et al, 2007), pitcher plants (Baiser et al, 2011) andtree-holes (Blakely et al, 2012), and are considered the main predators in the phytotelmata of several bromeliad species, where they exert a great influence on microorganisms (Walker et al, 2010;Baiser et al, 2011). Although several studies show that zygoptera larvae are the main aquatic predators within phytotelmata (Petermann et al, 2015a;Romero et al, 2016), in the bromeliads used in our study no larval forms of these organisms were observed. Paradise (2000) suggest that alterations in pH due to the decomposition of organic matter by Scirtidae larvae (Coleoptera) within phytotelmata may lead to a reduction in the mortality and an increase in the abundance of Diptera larvae in this habitat.…”
Section: Discussioncontrasting
confidence: 52%
“…Diptera larvae are very abundant in bromeliads (Araújo et al, 2007), pitcher plants (Baiser et al, 2011) andtree-holes (Blakely et al, 2012), and are considered the main predators in the phytotelmata of several bromeliad species, where they exert a great influence on microorganisms (Walker et al, 2010;Baiser et al, 2011). Although several studies show that zygoptera larvae are the main aquatic predators within phytotelmata (Petermann et al, 2015a;Romero et al, 2016), in the bromeliads used in our study no larval forms of these organisms were observed. Paradise (2000) suggest that alterations in pH due to the decomposition of organic matter by Scirtidae larvae (Coleoptera) within phytotelmata may lead to a reduction in the mortality and an increase in the abundance of Diptera larvae in this habitat.…”
Section: Discussioncontrasting
confidence: 52%
“…The dominant predators in the bromeliad phytotelmata are often damselfly nymphs (Odonata: Zygoptera), which are large-bodied relative to their prey, voracious generalists, and have been demonstrated to be sensitive to habitat size in several sites (Petermann et al 2015, Romero et al 2016. Bromeliads contain a food web based on fallen leaf litter supporting macroinvertebrate prey species -composed of detritivores feeding directly on leaf litter, as well as filterers and grazers on algae and the microbial community -and predators.…”
mentioning
confidence: 99%
“…, Romero et al. ), a decrease in the biomass of this functional group might lead to changes in the shape of trophic pyramids (Fig. c, d).…”
Section: Introductionmentioning
confidence: 77%
“…, Romero et al. ). A larger biomass ratio of predators in relation to prey causes greater interaction strength in a food web (Berlow et al.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation